A Systematic Analysis of Malawi's Girl-Centred Education Programming - John Foster Jill Moyo (Richtmann Publishing, 2022)
The aim of the systematic review was to compile and synthesise evidence on the contributions and implications of girl-centric policies and specialised interventions for girls' education in terms of access and participation. The results of the review confirm that girls' education programmes designed and implemented in a gender-based framework are effective in increasing girls' access to education. The results support the hypothesis that gender-centric policies and affirmative action interventions are sincere attempts to improve equity within education systems in Malawi. Despite these findings, the article argues that gender-centric policies and programmes can be replete with unfounded and contradicting assumptions about the nature of gender and egalitarian programming, which may negate the agenda on gender equality. The article also contends that even though great progress has been made in developing and adopting gender-sensitive education policies, feminist approaches have complicated implementation of the resulting gender-sensitive educational interventions. One of the main challenges in implementing feminist frameworks is in resolving the unquestioned and inconsistent assumptions about gender and egalitarian programming that have led to replication of affirmative action programmes that are only marginally effective. From the emanating perspectives, the article opiniates that general restorative interventions can be better approaches for overcoming gender inequality, and thus argues that girl-centric frameworks are unsustainable and must be supplanted with gender-as-equity paradigms. Received: 2 August 2022 / Accepted: 27 October 2022 / Published: 5 November 2022